(untitled) (International Journal of Engineering Sciences & Management Research, 2019)
Powder metallurgy technology requires maximum simplification of the shape of components which has a considerable effect on the design of the press mold, determining the production costs of the process as a whole, especially under the conditions of individual and small-series production. Powder metallurgy technology requires maximum simplification of the shape of components which has a considerable effect on the design of the press mold, determining the production costs of the process as a whole, especially under the conditions of individual and small-series production.